Relationship between clinical and radiological signs of bronchiectasis in COPD patients: results from COSYCONET - Kahnert, Kathrin; Jörres, Rudolf A.; Kauczor, Hans-Ulrich; Biederer, Jürgen; Jobst, Bertram; Alter, Peter; Biertz, Frank; Mertsch, Pontus; Lucke, Tanja; Lutter, Johanna I.; Trudzinski, Franziska; Behr, Jürgen; et al. (Respiratory medicine, 2020)
Bronchiectasis (BE) might be frequently present in COPD but masked by COPD symptoms. We studied the relationship of clinical signs of bronchiectasis to the presence and extent of its radiological signs in patients of different COPD severity. Visit 4 data (GOLD grades 1-4) of the COSYCONET cohort was used. Chest CT scans were evaluated for bronchiectasis in 6 lobes using a 3-point scale (0: absence, 1: ≤50%, 2: >50% BE-involvement for each lobe). 1176 patients were included (61%male, age 67.3y), among them 38 (3.2%) with reported physicians’ diagnosis of bronchiectasis and 76 (6.5%) with alpha1-antitrypsin deficiency (AA1D). CT scans were obtained in 429 patients. Within this group, any signs of bronchiectasis were found in 46.6% of patients, whereby ≤50% BE occurred in 18.6% in ≤2 lobes, in 10.0% in 3-4 lobes, in 15.9% in 5-6 lobes; >50% bronchiectasis in at least 1 lobe was observed in 2.1%. Scores ≥4 correlated with an elevated ratio FRC/RV. The clinical diagnosis of bronchiectasis correlated with phlegm and cough and with radiological scores of at least 3, optimally ≥5. In COPD patients, clinical diagnosis and radiological signs of BE showed only weak correlations. Correlations became significant with increasing BE-severity implying radiological alterations in several lobes. This indicates the importance of reporting both presence and extent of bronchiectasis on CT. Further research is warranted to refine the criteria for CT scoring of bronchiectasis and to determine the relevance of radiologically but not clinically detectible bronchiectasis and their possible implications for therapy in COPD patients.